Anthropometric Markers, Visceral Adipocyte Index, Inflammation Markers and Bone Density in Reproductive Obese Women - Meita Hendrianingtyas; Lisyani B.Suromo; Tri Indah Winarni (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2022)
Background: Obesity has been associated with the risk of various diseases. The correlation between anthropometry and bone health is complex. Visceral adipocyte index (VAI) is one of the compositions of body fat compositions that mostly associated with proinflammatory cytokine, which can stimulate C- reactive protein (CRP) that affects bone density.Objectives: This study aimed to prove the correlation between VAI, CRP and BMD in Asian reproductive obese womenMaterials and Methods: A cross sectional study was conducted in November 2020 - February 2021 and a total of 134 women of reproductive age with obesity participated in this study. Weight, height, body mass index (BMI) and rate of visceral fat were measured by body composition analyzer. Waist (WC) and hip circumferences (HC) measured by using tape; lipid profile and CRP level were examined using a clinical chemistry automatic analyzer, and the examination of bone mineral density (BMD) using dual-energy x-ray absorptiometry. Waist to hip ratio (WHR)and VAI calculated manually. Pearson and Spearman test were used for statistical analysis.Results: There were positive weak correlations between weight, height, BMI, WC, HC, rate of visceral fat, WHR and VAI. There were weak positive correlations between HC, WHR and CRP. There were positive moderate correlations between weight, height, BMI, waist, visceral fat, WHR and CRP. Conclusion: Although there were correlations between anthropometric parameters and VAI and also CRP, but we did not found correlation between VAI and CRP to all BMD parameters.